An analytical approach to supplier selection problem. (1st January 2014) - ,; Kumar, Darshan
Supplier selection and evaluation are arguably one of the most critical functions for the success of an organisation in today's competitive scenario. Both qualitative and quantitative factors have to be considered and a trade off is made between tangible and intangible factors while selecting a supplier. This selection is one of the decisions which determine the long-term viability of the organisation. Literature reveals that many methods have been used to objectively evaluate suppliers including analytic hierarchy process (AHP). AHP has been proposed in this paper for supplier selection for a textile industry. The criteria and sub-criteria for alternate suppliers have been taken by a study of a real problem with the help of engineers working in production, purchase and quality control departments of the concerned industry.